Hubungan Dukungan Keluarga dengan Tingkat Kemandirian Pasien Pasca Stroke - Nursyahfitri Rizky Ramadhani; Didi Kurniawan; Yesi Hasneli N (Jurnal Ilmiah Wahana Pendidikan, 2022)
stroke is complicated problem which afflicted by someone and being implied by his/her family to recover. The family supports has a significant roles in relation to enhance patient self-independence to face daily activities. This research aims at comprehending the correlation between family supports and the degree of patient independence on post-stroke. The research design applied is descriptive-correlation by using cross-sectional approach toward the sum of sample is 45 patient gained through Accidentally Sampling collection data of sampling as the criteria inclusion. The findings are most of patients gained fully-family supports get high degree of their self-independence is (54,4%), on the other hand, the patients which gain low-family supports so that having the highest degree, including low dependence (69%). The majority of the post-stroke patients gaining family fully-supports get hight self- dependence.